“Stego-analysis chain, session two” novel approach of stego-analysis system for image file - Naji, Ahmed Wathik; Hameed, Shihab A.; Islam, Md. Rafiqul; Zaidan, B .B.; Gunawan, Teddy Surya; Zaidan, A.A. (2009)
Stenography systems has too many approaches, it has a lot of applications and different ways, too many type of attackers have been tried to attacked the information that already embed in the carrier, however there is not yet a real stego- analysis system offered, the goal of this chain is to have too many investigations on the stego analysis systems, this paper will focus on the image file, the earlier tests showing that we may use the histogram habits to classify the image in to image carried data hidden and original image, the study will focus in to two main idea, the first idea, on the colour image, the colour start become grouping parallel with the increasing of the data hidden and the second feature on the gray level image, the histogram in the original image was pure without colours, after the embedding method has been applied there are many colour start to appears as shown down in the histogram, we will try through this paper to offer a new stego-analysis system though study the habits of the histogram.